2006
DOI: 10.1158/0008-5472.can-06-3562
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-Deficient Mice Have an Increased Susceptibility to Dextran Sulfate Sodium–Induced Colitis

Abstract: Inflammatory bowel diseases, chronic inflammatory disorders, have been strongly linked with an increased risk of the development of colorectal cancer. Understanding the etiology of these diseases is pivotal for the improvement of currently available strategies to fight against inflammatory bowel disease, and more importantly, to prevent colorectal cancer. Nuclear factor-erythroid 2-related factor 2 (Nrf2) has been known to be a transcriptional factor which plays a crucial role in cytoprotection against inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
308
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(326 citation statements)
references
References 20 publications
15
308
1
2
Order By: Relevance
“…Recent research indicates that Nrf2 plays a strong anti-inflammatory role in many different tissues via inhibition of the NF-B signaling pathway. Nrf2 plays a protective role in inflammationmediated colonic tumorigenesis (11), allergen-mediated airway inflammation (12), cigarette smoke-induced emphysema (13), and dextran sulfate sodium-mediated colitis (14). However, the role of Nrf2 in the inflammation of dystrophic muscles and whether Nrf2 may inhibit NF-B signaling pathway in patients with DMD are still unknown.…”
Section: Inflammation Is Widely Distributed In Patients Withmentioning
confidence: 99%
“…Recent research indicates that Nrf2 plays a strong anti-inflammatory role in many different tissues via inhibition of the NF-B signaling pathway. Nrf2 plays a protective role in inflammationmediated colonic tumorigenesis (11), allergen-mediated airway inflammation (12), cigarette smoke-induced emphysema (13), and dextran sulfate sodium-mediated colitis (14). However, the role of Nrf2 in the inflammation of dystrophic muscles and whether Nrf2 may inhibit NF-B signaling pathway in patients with DMD are still unknown.…”
Section: Inflammation Is Widely Distributed In Patients Withmentioning
confidence: 99%
“…Nrf2-deficient lymphocytes displayed enhanced proliferation, relative to WT lymphocytes, after anti-CD3 stimulation, demonstrating a direct influence of Nrf2 genotype on the activity of cells important in the adaptive immune response. 18 Similarly, Khor et al 21 very recently demonstrated increased expression of proinflammatory cytokines in colons of N0 mice, relative to WT mice, in response to challenge with DSS. Collectively, these studies implicate an important role of Nrf2 in attenuating proinflammatory signaling and colonic inflammatory cell infiltration in response to inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 92%
“…Cumulative evidence supports that ROS may function as mediators for aggravation of symptoms and pathophysiological responses in ulcerative colitis 19,20 . In mice, deficiency of nuclear factor erythroid-2-related factor-2 (Nrf2), a redox-sensitive transcriptional factor that regulates antioxidant genes 36 , or an impaired superoxide dismutase activity 18 has been reported to increase susceptibility to DSS-induced colitis, indicating a major role of antioxidants in protecting the intestine against ROS in colitis. Notably, 100 μM H 2 O 2 induced cell death in only 20% of U937 cells 14 but induced submaximal activation of CXCL8 transcription (nearly 80% maximum; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%